The Impact of an Intensive English Reading Course Based on the Production-Oriented Approach on the L2 Motivational Self System Among Chinese University English Majors From a Dynamic Systems Theory Perspective - Li, Chili; Zhou, Chujia; Zhang, Wen (Frontiers in Psychology, 2022)
This paper reports on a study that took a Dynamic Systems Theory (DST) perspective to second language motivational self system (L2MSS). More specifically, it investigated the influence of an Intensive English Reading course based on the Production-oriented Approach (POA) upon Chinese university English majors’ L2MSS from the DST perspective. To this end, two intact classes composed of 50 students were assigned into Experimental Group (N=23) and Control Group (N=27), who responded to an L2MSS scale before and after the one-semester intervention. Eight and five students were respectively selected using the purposive sampling method from the Experimental and Control Groups for follow-up semi-interviews. The quantitative results revealed that the overall and the dimensional (Ideal L2 Self and L2 Learning Experience) levels of L2MSS were significantly strengthened over time in the Experimental Group while kept stable in the Control Group. The qualitative results suggested that the participants’ enhanced Ideal L2 Self stemmed from an attractor basin that was deepened by a number of attractors encompassing Output Tasks and Peer Performance. The interview results also showed that the learners’ increased L2 Learning Experience pertained to an attractor basin that was consolidated by an array of attractors containing Output Tasks, Teacher Guidance, Group Discussion and Peer Assessment. The findings indicated that the attractors at the subjective and social dimensions in the POA-based course collectively worked together to cause the changes in L2MSS among the participants. The implications for intervening L2 motivation from a POA approach in EFL/ESL classrooms were discussed.